A rare case of uterine myxoid leiomyosarcoma - Dulewad, Shirish S.; Bhat, Varsha Narayana; Koli, Prachi V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Myxoid leiomyosarcoma is an uncommon tumour and in most cases, it is recognised only after the surgery. A 65 years old female patient got admitted at our hospital with history of rapidly growing abdominal mass with pain in abdomen since last 3 months. During abdominal examination 32 weeks huge mass was noted and on prevaginal examination mass couldn’t be separated from uterus. LDH was elevated, USG suggestive of vascular tumour of with neoplastic etiology of ovarain origin. CECT was done and findings suggestive of uterine adenocarcinoma with peritoneal carcinomatosis. Exploratory laparotomy with total abdominal hysterectomy with bilateral salphingoopherectomy with omentectomy with debulking surgery was performed. HPR reports suggestive of myxoid leiomyosarcoma with mitotic index of 10 with tumour cell necrosis suggestive of poor prognosis. Post-operative period patient had developed sudden myocardial infarction and shifted to ICU where she died due to ventricular fibrillation.